Food banks and the production of scarcity. Issue 1 (3rd October 2019) - May, Jon; Williams, Andrew; Cloke, Paul; Cherry, Liev
Abstract : This paper contributes to critical discussions of austerity by examining the constructions of scarcity that underpin it. Specifically, it shows how notions of scarcity (re)emergent in a period of austerity have shaped materially insufficient and stigmatising welfare systems. We do this through the example of UK food banks. We suggest that under austerity a particular moral economy of scarcity has become embedded at the level of common sense, including in the common sense of many of those distributing food aid. In UK food banks this moral economy is shaped by images of the "empty cupboard" and discourses of absolute hunger which normalise practices of (self)rationing and exacerbate food insecurity. Tracing attempts by some food bank managers and volunteers to challenge this moral economy, we conclude with a critical agenda for academics and practitioners to rethink relationships between welfare, austerity, and scarcity. Abstract : This paper seeks to contribute to critical discussions of austerity by examining the constructions of scarcity that underpin it. Using the example of food banks in the UK, we show that under austerity a particular moral economy of scarcity has become embedded at the level of common sense, including in the common sense of many of those distributing food aid, resulting in materially insufficient and stigmatising welfare systems. Tracing attempts by some food bank managers and volunteers to challenge this moral economy and the damaging practices it gives rise to, we conclude with a critical agenda for academics and practitioners to rethink relationships between welfare, austerity, and scarcity.